Overlapping LQT1 and LQT2 phenotype in a patient with long QT syndrome associated with loss-of-function variations in KCNQ1 and KCNH2 - Cordeiro, Jonathan M.; Perez, Guillermo J.; Schmitt, Nicole; Pfeiffer, Ryan; Nesterenko, Vladislav V.; Burashnikov, Elena; Veltmann, Christian; Borggrefe, Martin; Wolpert, Christian; Schimpf, Rainer; Antzelevitch, Charles (Canadian journal of physiology and pharmacology, 2010)
Long QT syndrome (LQTS) is an inherited disorder characterized by prolonged QT intervals and potentially life-threatening arrhythmias. Mutations in 12 different genes have been associated with LQTS. Here we describe a patient with LQTS who has a mutation in KCNQ1 as well as a polymorphism in KCNH2. The proband (MMRL0362), a 32-year-old female, exhibited multiple ventricular extrasystoles and one syncope. Her ECG (QT interval corrected for heart rate (QTc) = 518ms) showed an LQT2 morphology in leads V4-V6 and LQT1 morphology in leads V1-V2. Genomic DNA was isolated from lymphocytes. All exons and intron borders of 7 LQTS susceptibility genes were amplified and sequenced. Variations were detected predicting a novel missense mutation (V110I) in KCNQ1, as well as a common polymorphism in KCNH2 (K897T). We expressed wild-type (WT) or V110I Kv7.1 channels in CHO-K1 cells cotransfected with KCNE1 and performed patch-clamp analysis. In addition, WT or K897T Kv11.1 were also studied by patch clamp. Current-voltage (I-V) relations for V110I showed a significant reduction in both developing and tail current densities compared with WT at potentials >+20 mV (p < 0.05; n = 8 cells, each group), suggesting a reduction in IKs currents. K897T- Kv11.1 channels displayed a significantly reduced tail current density compared with WT-Kv11.1 at potentials >+10 mV. Interestingly, channel availability assessed using a triple-pulse protocol was slightly greater for K897T compared with WT (V0.5 = -53.1 ± 1.13 mV and -60.7 ± 1.15 mV for K897T and WT, respectively; p < 0.05). Comparison of the fully activated I-V revealed no difference in the rectification properties between WT and K897T channels. We report a patient with a loss-of-function mutation in KCNQ1 and a loss-of-function polymorphism in KCNH2. Our results suggest that a reduction of both IKr and IKs underlies the combined LQT1 and LQT2 phenotype observed in this patient.
Gesehen am 16.06.2023